The Effect of Green Color Breathing Therapy on Blood Pressure in Patients at Risk of Hypertensive Crisis - Noor Fitriyani; Firman Prastiwi; Siti Mardiyah (PT Inovasi Pratama Internasional, 2023)
Background: About 71% of non-communicable diseases (PTM) cause death, one of which is hypertension. The later phases of hypertension are the increased risk of hypertensive crisis, occurring in all types of hypertensions. Hypertensive crisis is a medical emergency and requires appropriate management. Non-pharmacological management is a complementary therapy to pharmacological therapy, one of which is green color breathing therapy. Objective: This study aims to determine the effect of green color breathing therapy on blood pressure in patients at risk of hypertensive crisis. Methods: This study used the pre and post-test method without control group design. The measuring instrument for this study used SOP green color breathing therapy and evaluated blood pressure with a sphygmomanometer. The research sample used a total sampling of 31 respondents. Bivariate data analysis using the Wilcoxon test. Results: Based on statistical tests with analysis of the Wilcoxon Test (p=0.001). This shows that the p value <0.05, there is a significant effect of green color breathing therapy on the blood pressure of patients at risk of hypertensive crisis. Conclusion: Green color breathing therapy can reduce blood pressure in patients at risk of hypertensive crisis.